Changes in melanocyte RNA and DNA methylation favour pheomelanin synthesis and may avoid systemic oxidative stress after dietary cysteine supplementation in birds - Rodríguez-Martínez, Sol (2019)
© 2019 John Wiley & Sons Ltd.